BIOTECHNOLOGY FOR PURIFYING WASTEWATER CONTAMINATED WITH PETROLEUM PRODUCTS USING THE AQUATIC PLANT EICHHORNIA (Scientific journal of the Fergana State University, 2025)
This article provides a briyef analysis of research on wastewater treatment using the aquatic plant Eichhornia (Eichhornia crassipes Solms., Pontederiaceae). It also includes information about the purification of wastewater contaminated with oil and petroleum products in two water treatment facilitiyes at Fergana Refinery LLC, located in the Fergana region. Additionally, the article presents details on the analysis of samples collected for studying wastewater treatment at the plant and the results of these analyses.